2020
DOI: 10.1371/journal.pone.0239977
|View full text |Cite
|
Sign up to set email alerts
|

Inertial flywheel knee- and hip-dominant hamstring strength exercises in professional soccer players: Muscle use and velocity-based (mechanical) eccentric overload

Abstract: The primary aim of the present study was to analyze mechanical responses during inertial knee-and hip-dominant hamstring strengthening exercises (flywheel leg-curl and hip-extension in conic-pulley), and the secondary aim was to measure and compare regional muscle use using functional magnetic resonance imaging. Mean power, peak power, mean velocity, peak velocity and time in the concentric (CON) and eccentric (ECC) phases were measured. The transverse relaxation time (T2) shift from pre-to post-exercise were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 52 publications
1
20
1
Order By: Relevance
“…In contrast to the present findings, other investigations reported that no eccentric overload was obtained when using a unilateral (Suarez-Arrones et al, 2020) or bilateral flywheel leg curl (Tous-Fajardo et al, 2006). Although the moment of inertia (0.072 kg•m 2 ) used previously in unilateral protocols is within the range of the present investigation (0.029-0.089 kg•m 2 ), other factors may have influenced the outcomes between investigations.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to the present findings, other investigations reported that no eccentric overload was obtained when using a unilateral (Suarez-Arrones et al, 2020) or bilateral flywheel leg curl (Tous-Fajardo et al, 2006). Although the moment of inertia (0.072 kg•m 2 ) used previously in unilateral protocols is within the range of the present investigation (0.029-0.089 kg•m 2 ), other factors may have influenced the outcomes between investigations.…”
Section: Discussioncontrasting
confidence: 99%
“…Specifically, the participants' flywheel training experience, the device characteristics and technique utilized are important to consider (Muñoz-López et al, 2021a). For example, considering the need for a maximal and prolonged familiarization to optimize eccentric peak power outputs (Sabido et al, 2018;Piqueras-Sanchiz et al, 2020), the submaximal familiarization (2 sets of 6-8 submaximal repetitions) previously utilized may have influenced eccentric peak power obtained (Suarez-Arrones et al, 2020). The present investigation reports that an eccentric overload of peak power may be achieved regardless of moment of inertia utilized with unilateral flywheel leg curl after sufficient familiarization (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, exercise selection should be considered by practitioners to optimally design their training programs. Multi-joint exercises such as the flywheel squats, deadlifts, and lunges should be prioritized in training sessions seeking strength and power development (Maroto-Izquierdo et al, 2017b ; Beato and Dello Iacono, 2020 ; Madruga-Parera et al, 2020 ), in particular because greater transfer from strength training to sports performance occurs, while less functional single-joint exercises such as the flywheel leg curl and flywheel hip extension (Askling et al, 2003 ; Piqueras-Sanchiz et al, 2020 ; Suarez-Arrones et al, 2020 ; Beato et al, 2021 ) may be preferentially used as injury prevention exercises.…”
Section: Flywheel Training Periodization In Team Sportsmentioning
confidence: 99%
“…Technological devices are available to allow quantitative visualization of the effort of an individual, by recording repetition velocity (Jovanovic and Jukic, 2020). Research and practical application of VBT are becoming increasingly popular in S&C and, when VBT is applied systematically, it allows for an immediate feedback, a fatigue control, and the monitoring of biomechanical changes, and can guide the training process (Banyard et al, 2020;Lahti et al, 2020;Martinez-Cava et al, 2020;Perez-Castilla et al, 2020;Sindiani et al, 2020;Suarez-Arrones et al, 2020;Tsoukos et al, 2020). However, for obtaining accurate measurements, individuals must perform fast concentric actions with a good technique, and training adherence and motivation, which may be a barrier for use in rehabilitation (Kawamori et al, 2006).…”
Section: Velocity-based Trainingmentioning
confidence: 99%